Upaya Mewujudkan Persatuan dan Toleransi Mengantisipasi Bullying dan Deskriminasi di SMK Al-Washliyah 3 - Sahrinal, Sahrinal; Salmazahra A. P, Sarah; Sallina, Siti; Fatimah, Siti; Siregar, Aqil Indrardi; Dafinda, M.Difa; Ramadhan, Zilan; Arsal, M. Abli; Hasanah, Uswatun; Ramadhan, Nadyra; Nirmawan, Nirmawan (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Bullying is a form of violent behavior with the power to hurt a person or group verbally, physically, or psychologically the victim. The impacts experienced by victims of bullying are having various mental problems and physical health complaints. This study uses a qualitative descriptive research method that aims to obtain a picture of family social support for adolescent victims of bullying so that they can restore their social functioning and regain their self-confidence so that they can carry out their roles in society as usual. The data collection technique used was a document study located at SMK Al Washliyah 3 Medan. The results of the study showed that 2 dimensions of physical and verbal bullying were found at SMK Al-Washliyah 3 Medan. In the physical bullying dimension, 3 students experienced hiding of goods and 2 students experienced tripping. There were 15 students who experienced the verbal bullying dimension, namely 5 students experienced being teased, 5 students experienced being called with names they didn’t like, and 5 students experienced being called by their parents’ names. Physical and verbal bullying are forms of aggressive behavior that have a negative impact on victims. Physical bullying includes direct actions such as hitting, kicking, or damaging the victim’s belongings while verbal bullying involves insults, teasing, or giving derogatory nicknames.